2011
DOI: 10.1007/s11368-011-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

In situ quantification of CH4 bubbling events from a peat soil using a new infrared laser spectrometer

Abstract: To cite this version:Sébastien Gogo, Christophe Guimbaud, Fatima Laggoun-Défarge, Valéry Catoire, Claude Robert. In situ quantification of CH4 bubbling events from a peat soil using a new infrared laser spectrometer. Journal of Soils and Sediments, Springer Verlag, 2011, 11 (4) Results and discussionThe results show that the CH 4 emissions estimated with the SPIRIT are consistent with those already published. The high emissions, both through diffusion and bubbling in the Eriophorum plot, were on the same ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…At the two DFE sites, CO 2 effluxes were of similar magnitude; however, substantial differences were observed in the magnitude of CH 4 effluxes ( Table 2). At both sites the occurrence of CH 4 effluxes was closely tied to soil conditions and contaminant availability (i.e., locations of high moisture content where DFE pooled and was not excavated; Figures 4, 5), suggesting that the occurrence of CH 4 effluxes is related to specific conditions rather than only fuel type, consistent with the measurement of CH 4 effluxes in natural wetland and bog environments (Gogo et al 2011). Comparison of emission rates between the two field sites showed that CH 4 effluxes at the Cambria site were an order of magnitude greater than those measured at the Balaton site, pointing to rapid DFE degradation at the Cambria site.…”
Section: Results and Discussion Composition And Magnitude Of Gas Emissupporting
confidence: 72%
“…At the two DFE sites, CO 2 effluxes were of similar magnitude; however, substantial differences were observed in the magnitude of CH 4 effluxes ( Table 2). At both sites the occurrence of CH 4 effluxes was closely tied to soil conditions and contaminant availability (i.e., locations of high moisture content where DFE pooled and was not excavated; Figures 4, 5), suggesting that the occurrence of CH 4 effluxes is related to specific conditions rather than only fuel type, consistent with the measurement of CH 4 effluxes in natural wetland and bog environments (Gogo et al 2011). Comparison of emission rates between the two field sites showed that CH 4 effluxes at the Cambria site were an order of magnitude greater than those measured at the Balaton site, pointing to rapid DFE degradation at the Cambria site.…”
Section: Results and Discussion Composition And Magnitude Of Gas Emissupporting
confidence: 72%
“…Because of relatively high amounts of submerged vegetation (peak biomass density 0.43 kg m −2 ) [ Gu et al , ], Dongtaihu Bay and the East Zone, the two shallow water zones bear some resemblance to wetland ecosystems. In wetlands, ebullition emission comprises only 13 to 48% of the total CH 4 flux [ Gogo et al , ; Maeck et al , ; Crawford et al , ]. However, the difference in the ebullition contribution between MLW and BFG is not statistically significant ( p = 0.20).…”
Section: Discussionmentioning
confidence: 99%
“…The instrument description and method for CH 4 and N 2 O concentration retrieval are reported in Guimbaud et al (2011). SPIRIT has demonstrated high precision for CH 4 and N 2 O mixing ratio measurement in ambient air (0.2% for 1.5 sec of integration time, namely ∼ 4 ppb for CH 4 at 1.9 ppmV and ∼ 0.6 ppb for N 2 O at 320 ppbV) as well as for flux emission measurements above peatlands, lakes, and cultivated fields, using the closed chamber method (Guimbaud et al, 2011;Gogo et al, 2011).…”
Section: Instrument Descriptionmentioning
confidence: 99%